Pengenalan Perangkat Keras Komputer Menggunakan Game Tebak Gambar Berbasis Web Di Rumah Baca RAKUS - Rizky Hanifudin; Putri Rokhmayati; M Fadhly Noor Rizqi; Rizky Destyan Pulunggono; Wardah Oktafiani; Iqbalsyah Khatami; Tritya Adi Dharma; Satria Banistama; Salwa Carelina Maybrella; Andini Gustiani (Abdi Jurnal Publikasi, 2023)
In an era of rapid technological development like today, we are entering the 4.0 revolution era where technology is used in various fields, the dependence on technology is increasing in various circles, and ages. With the increasing dependence on technology in various circles and ages, therefore we should introduce technology to children as early as possible. Such as introducing what a computer is, introducing the basics of computer equipment and so on. To introduce the basics of computer equipment to children, of course, with the right method so that children can easily understand and also not get bored with the introduction method. The RAKUS Reading House (Library Bookshelf) is a reading house that houses a relatively large number of children, located in Bojong Indah, Parung Bogor. Most of the children at the RAKUS Reading House (Library Bookshelf) still do not have a basic understanding of the basics of computer equipment. On average, children only know the shape of the device without a deeper understanding of the names and uses of existing computer devices. In order to be able to implement a method of introducing the basics of computer hardware to children so that it is easy to understand and not boring, we are working with Rumah Baca RAKUS (Library Bookshelf) to hold activities to introduce computer hardware to children. In this activity we use a web-based picture guessing game. By holding community service (PKM) it is hoped that it can help the children of the RAKUS Reading House (Library Bookshelf) to recognize and understand the basics of computer equipment, of course, in a fun and fun way. So that in the future the children can prepare more maturely for provisions to a higher level of education.